Spring field reports - Thompson, Carol A.et al (1985)
Field notes contributed by Carol A. Thompson listing bird sightings, predominately in northwestern Iowa. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly Report of spring 1985. Epson - sheet feed/flatbed